(untitled) (Revista Sistemas de Producción Agroecológicos, 2024)
Due to the high costs of animal feed concentrates, sheep producers have been forced to seek alternatives to make their production systems more efficient by improving forage use, which has driven the adoption of new technologies. Among these, probiotics, which are microorganisms added to the feed, have proven beneficial for ruminal digestion without altering physiological functions. In this context, the present study determined the effect of Lactobacillus acidophilus and Saccharomyces cerevisiae on the in vitro digestibility of five forages used in sheep feeding. Samples were taken from hibiscus (Hibiscus rosa-sinensis), moringa (Moringa oleifera), gliricidia (Gliricidia sepium), mulberry (Morus alba), and the king grass hybrid (Pennisetum purpureum x Pennisetum typhoides). The treatments were organized into two groups: one without microorganisms (WMI) and the other with microorganisms (WMIcro). The inoculum was obtained from the excreta of grazing sheep, which were collected via rectal palpation and then mixed with buffer solution (McDougall’s saliva). Subsequently, the microorganisms (Lactobacillus acidophilus and Saccharomyces cerevisiae), which were previously macerated and homogenized, were added. The microorganisms or probiotics, the inoculum, and the samples were placed in 20 ml syringes and incubated at constant temperature and agitation for 48 hours, then dried in an oven at 60°C for 48 hours. In vitro digestibility of dry matter (IVDMD), neutral detergent fiber (IVNDFD), and crude protein (IVCPD) were determined. The results were analyzed with SPSS software. Hibiscus, mulberry, moringa, and gliricidia showed significant differences (P<0.05) between WMIcro and WMI treatments in IVDMD, being higher in treatments without probiotics (75.6% vs. 41.9%), (70.1% vs. 32.7%), (70.1% vs. 27.6%), and (66.9% vs. 48.2%), respectively. The IVNDFD of WMIcro and WMI treatments for hibiscus, mulberry, and king grass showed significance (P<0.05), being higher in SMI (72.9%, 68.9%, and 32.2%, respectively); no effects were observed in gliricidia and moringa when probiotics were used. The IVCPD of mulberry, hibiscus, moringa, and king grass were higher (P<0.05) in the treatment without probiotic (SP) (73.7%, 64.7%, 63.3%, and 35.8%, respectively). No effect was observed in gliricidia WMI and WMIcro (60.65% and 59.95%). The correlation between IVDMD in the WMI treatment compared to IVCPD in the WMI treatment was 0.95, which indicates that as the Dry Matter (DM) value increases, so does the Crude Protein value; a similar trend was observed in neutral detergent fiber. This research determined that probiotics improve the digestibility of the forage species used. It is concluded that the probiotics did not have a positive effect on IVDMD, IVNDFD, and IVCPD, with the values being higher (P<0.05) in hibiscus, mulberry, moringa, and king grass in the WMI treatments. The efficiency of the probiotics used in the present study cannot be entirely ruled out, despite the inconsistency of the results, as in vivo studies yield more favorable results for these microorganisms.